2022
DOI: 10.3389/fimmu.2022.882502
|View full text |Cite
|
Sign up to set email alerts
|

Multimericity Amplifies the Synergy of BCR and TLR4 for B Cell Activation and Antibody Class Switching

Abstract: Sustained signaling through the B cell antigen receptor (BCR) is thought to occur only when antigen(s) crosslink or disperse multiple BCR units, such as by multimeric antigens found on the surfaces of viruses or bacteria. B cell-intrinsic Toll-like receptor (TLR) signaling synergizes with the BCR to induce and shape antibody production, hallmarked by immunoglobulin (Ig) class switch recombination (CSR) of constant heavy chains from IgM/IgD to IgG, IgA or IgE isotypes, and somatic hypermutation (SHM) of variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Indeed, we observed an overall trend toward lower IgM levels in the rabbits that received GPC NPs, with IgM levels being significantly lower after the second immunization (median mean fluorescence intensity [MFI] of 67 versus 320, respectively; two-tailed Mann-Whitney U -test; p = 0.0022), consistent with observations that multivalent antigen presentation accelerates class-switching. 32 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we observed an overall trend toward lower IgM levels in the rabbits that received GPC NPs, with IgM levels being significantly lower after the second immunization (median mean fluorescence intensity [MFI] of 67 versus 320, respectively; two-tailed Mann-Whitney U -test; p = 0.0022), consistent with observations that multivalent antigen presentation accelerates class-switching. 32 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several viral proteins can activate TLR4 [ 13 ]. Recently, it was proposed that the multimeric or oligomeric structure of viral proteins is important for TLR4 activation [ 8 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several viral proteins can activate TLR4 [ 13 ]. Recently, it was proposed that the multimeric or oligomeric structure of viral proteins is important for TLR4 activation [ 8 , 13 ]. Although oligomeric M1 is abundant, monomeric M1 also exists at equilibrium in vitro and in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the present study, we omitted the previously used dimerization domain and found that HA could trimerize even in the absence of a foldon. The implication is trivalent display also of B cell epitopes, and that likely will facilitate cross-linking of BCR and efficient immune activation ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%